High catalytic activity of Rh nanoparticles generated from cobaltocene and RhCl3 in aqueous solution. Issue 10 (20th August 2019) - Wang, Wenjuan; Ciganda, Roberto; Wang, Changlong; Escobar, Ane; Martinez-Villacorta, Angel M.; Ramirez, Maria de los Angeles; Hernández, Ricardo; Moya, Sergio E.; Ruiz, Jaime; Hamon, Jean-René; Astruc, Didier
Abstract : Cobalticinium chloride-stabilized RhNPs are very efficient catalysts for hydrolysis of H3 N-BH3, reduction of 4-NP, hydrogenation of benzene and transfer hydrogenation. Abstract : Rh compounds including Rh nanoparticles are among the most active catalysts for many reactions. Catalytically very reactive small Rh nanoparticles have been generated upon reduction of aqueous RhCl3 by cobaltocene, characterized, and shown to be very efficient for the test nitrophenol reduction (compared to other metal NPs), generation of hydrogen from ammonia borane hydrolysis, transfer hydrogenation, and benzene hydrogenation. This useful concept of cobalticinium chloride-stabilized NP catalysts could potentially be efficiently applicable to a variety of other aqueous catalytic systems.